Technology and Innovation for Sustainable Development - Vos, Rob (The United Nations Series on Development, 2015)
This book is available as open access through the Bloomsbury Open Access programme and is available on bloomsburycollections.com. Continuation along current development pathways is not sustainable. Available technology and production practices and the consumption patterns of modern societies are leading to global warming and ecological destruction. Business as usual is not an option. There is an urgent need to find a new development paradigm that ensures environmental sustainability while managing to provide, now and in the future, a decent livelihood for all of humankind. In Technology and Innovation for Sustainable Development, experts in the area provide a variety of insights about the technical transformation needed for sustainable development. It spells out the behavioural and policy changes that would need to accompany the next technological transformation, taking into account the complexity of inducing technological change in the energy and agricultural sectors. The assessment suggests that this will require major, but doable improvements in national innovation systems and major, but affordable shifts in investment patterns and related macroeconomic adjustments.